TGF-β phospho antibody array identifies altered SMAD2, PI3K/AKT/SMAD, and RAC signaling contribute to the pathogenesis of myxomatous mitral valve disease - Andrew J. McNair; Greg R. Markby; Qiyu Tang; Vicky E. MacRae; Brendan M. Corcoran; Brendan M. Corcoran (Frontiers in Veterinary Science, 2023)
BackgroundTGFβ signaling appears to contribute to the pathogenesis of myxomatous mitral valve disease (MMVD) in both dogs and humans. However, little is known about the extent of the downstream signaling changes that will then affect cell phenotype and function in both species.ObjectiveIdentify changes in downstream signals in the TGFβ pathway in canine MMVD and examine the effects of antagonism of one significant signal (SMAD2 was selected).Materials and methodsCanine cultures of normal quiescent valve interstitial cells (qVICs) and disease-derived activated myofibroblasts (aVICs) (n = 6) were examined for TGFβ signaling protein expression using a commercial antibody array. Significant changes were confirmed, and additional proteins of interest downstream in the TGFβ signaling pathway and markers of cell phenotype were examined (PRAS40, S6K, elF4E IRS-1, αSMA, and VIM), using protein immunoblotting. RT-PCR examined expression of gene markers of VIC activation (ACTA2, TAGLN, and MYH10; encoding the proteins αSMA, SM22, and Smemb, respectively). Attenuation of pSMAD2 in aVICs was examined using a combination of RNA interference technology (siRNA) and the SMAD7 (antagonizes SMAD2) agonist asiaticoside.ResultsThe antibody array identified significant changes (P < 0.05) in 19 proteins, of which six were phosphorylated (p). There was increased expression of pSMAD2 and pRAC1 and decreased expression of pmTOR, pERK1/2, and pAKT1. Expression of pPRAS40 and pIRS-1 was increased, as was the mTOR downstream transcription factor pS6K, with increased expression of peIF4E in aVICs, indicating negative feedback control of the PI3K/AKT/mTOR pathway. SMAD2 antagonism by siRNA and the SMAD7 agonist asiaticoside decreased detection of pSMAD by at least 50%, significantly decreased expression of the aVIC gene markers ACTA2, TAGLN, and MYH10, and pαSMA, pAKT2, and pERK1, but had no effect on pS6K, pERK2, or pVIM expression in aVICs. SMAD2 antagonism transitioned diseased aVICs to normal qVICs, while maintaining a mesenchymal phenotype (VIM+) while concurrently affecting non-canonical TGFβ signaling.ConclusionMMVD is associated with changes in both the canonical and non-canonical TGFβ signaling pathway. Antagonism of SMAD2 transitions diseased-activated myofibroblasts back to a normal phenotype, providing data that will inform studies on developing novel therapeutics to treat MMVD in dogs and humans.